Effects of high-intensity interval training on physical and cognitive function in middle-aged male mice - Stephenson, Justin C.; Tran, Tuan D.; Graber, Ted G. (Frontiers in Aging, 2025)
IntroductionDeclining functional capacity, both physical and cognitive, is a consequence of aging. However, exercise is a promising intervention to mitigate normal age- related decline. Although numerous studies have elucidated the benefits ofexercise per se, the effect of high-intensity interval training (HIIT) on a middle-aged population is less well-studied.ObjectiveOur primary purpose was to assess the effect of 3 months of HIIT on physical and cognitive performance in middle-aged (17-month-old at the end) male C57BL/6J mice compared to sedentary controls (SED). We hypothesized that exercised mice would be resistant to age-related decline in cognitive and physical ability.MethodsTo measure physical function, we used the well-validated comprehensive functional assessment battery (CFAB) scoring system, comprised of determinants including voluntary wheel running, inverted cling, grip test, treadmill maximum speed, and rotarod performance. We measured cognition using open field test, novel object recognition, Y-maze, and puzzle box. Additional assessments included body composition (via MRI) and in vivo contractile physiology (plantar flexor torque).ResultsTraining resulted in significant improvements in aerobic capacity for the HIIT group, increasing treadmill time by 28%, while the SED group demonstrated a 41.4% decline in treadmill time. However, we found no significant differences in overall cognitive function. Contrary to our previous research in other age groups, the current study found a negligible effect of HIIT on body composition.DiscussionWe note that at 17 months of age, mice did not exhibit any evidence of cognitive deterioration in either group over the training period, thus potentially explaining the lack of an exercise effect. We found that HIIT had less influence on both physical and cognitive function than expected, which may be because function in this age group remains relatively stable. Future work will investigate the adult cognitive response to HIIT in older adults, at ages where there is well- documented cognitive decline.